The role of temperature in plasmon sensors in physical and biological research - LV Shmeleva; AD Suprun (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
Recently, sensors that use the phenomenon of plasmon resonance have been widely used [1]. In this case, biosensors are of particular interest [2]. The plasmon resonance method is attractive in that it has a sufficiently high sensitivity to changes in concentration (the most widespread use) of the medium under study (analyte). But this method can be no less attractive for research other properties. For example, the effects of temperature during laser irradiation. In such sensors, on the one hand, the temperature can significantly affect the frequency position of the plasmon resonance, which cannot be ignored. On the other hand, the "temperature effect" itself can be the basis for measuring physical quantities that are sensitive to temperature.